Exploring Entrepreneurship Education Effectiveness at British Universities – An Application of the World Café Method. (December 2021) - Decker-Lange, Carolin; Lange, Knut; Dhaliwal, Spinder; Walmsley, Andreas
Universities have made significant investments in entrepreneurship programs for decades, but the scope, relevance and usefulness of entrepreneurship education are still questioned. This study aims to explore the meaning of effectiveness as it relates to entrepreneurship education in a grounded and holistic sense, recognizing both the range of stakeholders involved in the design, delivery and experience of entrepreneurship education and the underlying complexity of the issue at hand. Two World Café events, a method designed to elicit grounded knowledge, were organized to seek insights from a diverse range of stakeholders. Results confirm and illustrate the complex nature of effectiveness in entrepreneurship education. The purpose of specific educational initiatives, diverse audiences' expectations and contextual factors must be considered in any meaningful attempt at identifying effectiveness. Findings also revealed a consensus that effectiveness relates to creating a transformational process, which leads to a shift in attitudes towards entrepreneurship. This shift prepares students for careers that go beyond the launch of a new venture. The role of time lags in assessing effectiveness was also identified. We suggest an agenda for future research and practical implications.